(untitled) (International journal of artificial intelligence, 2024)
Currently, everyone knows the role of psychoemotional factors in the development and course of socially significant, chronic dermatoses, in particular psoriasis. Various psychoemotional disorders, depression, fear, anxiety, etc. affect not only the recurrence and course of the dermatological process, which in turn is also one of the factors, but also significantly contribute to a decrease in the social activity of patients